State family policy and mechanisms for its implementation on regional level - Sitnik , Svitlana (Theory and Practice of Public Administration, 2019)
Studied the main directions of the state family policy, analysed the basic principles of the state family policy androle of the state in this poсess. The mechanisms of public administration, their priority tasks in the field of family policy, tendencies of improvement of the state regulation system of state family policy development are analysed.The purpose of state family policy is to provide favorable conditions for the comprehensive development of the family and its members, the most complete realization of the family functions and improvement of its standard of living, increase of the role of the family as the basis of society.The main principles of the state family policy are: the sovereignty and autonomy of the family in decision-making on their development, a differentiated approach to the provision of state guarantees of social protection of the family, parity and partnership between women and men in all spheres of life, social partnership of the family and the state, the priority of the interests of each child, regardless of the family in which it is brought up, the continuity of generations.Thus, the mechanisms of public administration in the field of family policy require legal and organizational improvement that would remove them from the situation of the extensive regime of family management and would provide a reorientation to the gradual, taking into account specific Ukrainian conditions and opportunities, the implementation of progressive practices in family policy management with the purpose of strengthening and developing the family as the social basis of the state The key concepts are: "State family policy", "family relations", "development environment", "State policy", "social infrastructure", "legal regulation", "social institution", "social group", "marginal families".